Employment Patterns in OECD Countries Reassessing the Role of Policies and Institutions - Bassanini, Andrea (OECD Economics Department Working Papers, 2006)
This paper explores the impact of policies and institutions on employment and unemployment of OECD countries in the past decades. Reduced-form unemployment equations, consistent with standard wage setting/price-setting models, are estimated using cross-country/time-series data from 21 OECD countries over the period 1982-2003. In the "average" OECD country, high and long-lasting unemployment benefits, high tax wedges and stringent anti- competitive product market regulation are found to increase aggregate unemployment. By contrast, highly centralised and/or coordinated wage bargaining systems are estimated to reduce unemployment. These findings are robust across specifications, datasets and econometric methods.